Pandangan Konstitusi Terhadap Notaris: (Studi Kasus Putusan MK terhadap Notaris) - Musri Nauli (Magister Kenotariatan, Universitas Jambi, 2019)
The Constitutional Court of the Republic of Indonesian cancel article 66 Law No. 30 of 2004, Act of Notary. The Constitutional Court of the Republic of Indonesian declare article 66 act of Notary contrary to the principle equality before the law. Consideration The Constitutional Court of the Republic of Indonesian interesting to view to how configuration right to refuse following the decision the Constitutional Court of the Republic of Indonesian